Natural killer cells modified with a Gpc3 aptamer enhance adoptive immunotherapy for hepatocellular carcinoma - Youshi Zheng; Zisen Lai; Bing Wang; Zuwu Wei; Yongyi Zeng; Qiuyu Zhuang; Xiaolong Liu; Kecan Lin (Discover Oncology, 2023)
Abstract Introduction Natural killer cells can attack cancer cells without prior sensitization, but their clinical benefit is limited owing to their poor selectivity that is caused by the lack of specific receptors to target tumor cells. In this study, we aimed to endow NK cells with the ability to specifically target glypican-3+ tumor cells without producing cell damage or genetic alterations, and further evaluated their therapeutic efficiency. Methods NK cells were modified with a Gpc3 DNA aptamer on the cell surface via metabolic glycoengineering to endow NK cells with specific targeting ability. Then, the G-NK cells were evaluated for their specific targeting properties, cytotoxicity and secretion of cytokines in vitro. Finally, we investigated the therapeutic efficiency of G-NK cells against glypican-3+ tumor cells in vivo. Results Compared with NK cells modified with a random aptamer mutation and unmodified NK cells, G-NK cells induced significant apoptosis/necrosis of GPC3+ tumor cells and secreted cytokines to preserve the intense cytotoxic activities. Moreover, G-NK cells significantly suppressed tumor growth in HepG2 tumor-bearing mice due to the enhanced enrichment of G-NK cells at the tumor site. Conclusions The proposed strategy endows NK cells with a tumor-specific targeting ability to enhance adoptive therapeutic efficiency in GPC3+ hepatocellular carcinoma.